Decoding regulatory associations of G-quadruplex with epigenetic and transcriptomic functional components - Fang, Shuyi; Liu, Sheng; Yang, Danzhou; Yang, Lei; Hu, Chang-Deng; Wan, Jun (Frontiers in Genetics, 2022)
G-quadruplex (G4) has been previously observed to be associated with gene expression. In this study, we performed integrative analysis on G4 multi-omics data from in-silicon prediction and ChIP-seq in human genome and classified potential G4 sites into three distinguished groups, including high-confidence G4-forming locations and one group only containing predicted G4 motif candidates. We explored the associations of different-confidence G4 groups with other epigenetic regulatory elements, including CpG islands, chromatin status, enhancers, super-enhancers, G4 locations compared to the genes, and DNA methylation. Our elastic net regression model revealed that G4 structures could correlate with gene expression in two opposite ways depending on their locations to the genes as well as G4-forming DNA strand. Some transcription factors were identified to be over-represented with G4 emergence. The motif analysis discovered distinct consensus sequences enriched in the G4 feet, the flanking regions of two groups of G4s. We found high GC content in the feet of high-confidence G4s when compared to high TA content in solely predicted G4 feet. Overall, we analyzed the genome-wide distribution properties of G4s and uncovered the comprehensive associations of G4 formations or predictions with other epigenetic and transcriptional mechanisms to coordinate gene transcription.